Habitat Management Based on Mangrove Sensitivity Assesment in Tulungagung Coastal Area - Dhira Kurniawan Saputra; Bambang Semedi; Arief Darmawan; Oktiyas Muzaky Luthfi; Muliawati Handayani; Sulastri Arsad (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
Tulungagung reflects the typical conditions of southern coast of Java, which dominated bay small bays with thin layer of superficial mud sediments and bordered by hilly terrain. Mangrove distribution in Tulungagung located in there locations, Brumbun Beach, Gerangan Beach and Sine Beach. This research aimed to identify the forest structure, habitat sensitivity and completed with management plan in each location. Data collected includes vegetation structure, hydrooceanography, environmental pressure and anthropogenic activities. An interesting finding is that, despite its narrow areas (2,24 Ha), mangroves in Tulungagung have high species diversity (11 species of true mangrove includes Acanthus ebracteatus, Acanthus ilicifolius, Acrostichum aureum, Avicennia alba, Avicennia marina, Ceriops tagal, Excoecaria agallocha, Rhizopora apiculata, Rhizopora mucronata, Rhizopora stylosa dan Sonneratia alba). Rm and Rs stands dominated by >7m height with canopy cover range from 79,4-89,6%. Geomorphological settings and limited mud supply are the primary challenges for mangrove habitat in Tulungagung. On the other hand, observation conservation status and local stakeholders involvement show the need for improvement of mangrove management in Tulungagung coastal areas.